Interaction of wind and hydropower: potential for compensation under seasonal fluctuations - Romеn A. Zahidov; Jaхongir Х. Mamadaliyev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: in recent decades, renewable energy sources (RES) have become increasingly important in global energy policy. Increasing energy demand, depletion of natural resources and climate change require a transition from traditional energy sources to more sustainable solutions. In this context, Central Asia and, in particular, Uzbekistan, face significant challenges due to limited water resources and growing demand for electricity. The energy system of Uzbekistan has long been dependent on fossil fuels and hydroelectric power plants, but climate change is increasingly leading to a decrease in water resources, which has a direct impact on the stability of hydropower. In conditions of dry seasons and climatic anomalies, the capacity of small hydroelectric power plants often becomes insufficient to meet the needs of the population and industry. In parallel with this, wind energy demonstrates sustainable potential in the climatic conditions of the region, providing stable electricity generation during periods of low water levels. The combined use of small hydropower plants (HPPs) and wind power plants (WPPs) can be a solution to ensure a stable energy supply, especially in conditions of water scarcity. This approach not only helps to reduce dependence on natural factors, but also reduces the carbon footprint, which is in line with sustainable development goals and allows for more efficient use of the potential of renewable energy sources. Aim: to research the status and potential of small hydroelectric power plants in Uzbekistan, as well as to explore the possibilities of compensating for seasonal fluctuations in hydroelectric power plant output by using wind power plants. The advantages of integrating wind energy are obvious: it can become a sustainable addition to hydropower, especially in the summer months when water resources are reduced. This study aims to assess the prospects for an integrated approach to the development of small hydroelectric power plants and wind power plants in the energy sector of Uzbekistan Methods: the main method of our study is to analyze and validate that with a decrease in energy production at small hydroelectric power plants, wind power plants can compensate for the total or partial reduction in potential are considered one of the most reliable methods for compensating the potential of small hydroelectric power plants at the expense of wind energy. Results: the analysis showed that small hydroelectric power plants in Uzbekistan experience significant seasonal fluctuations in capacity. In the summer months, the greatest decrease in productivity occurs due to a decrease in the level of water resources in rivers and canals. Wind energy data showed that in the summer months, when the capacity of small hydroelectric power plants decreases, the potential of wind turbines remains relatively stable. This makes wind power plants a promising solution for compensating for seasonal power deficits. Calculations showed that the capacity of wind power plants is sufficient to partially compensate for the decline in output at small hydroelectric power plants in the periodic period. This confirms the feasibility of including wind power plants in the overall energy balance to ensure a more stable energy supply.